Analysis of Cyanide in Bulbs of Gadung Crackers For sale in Pelem Village, Tulungagung Regency using Complex Formation Titration Method - Wattiheluw, Muhammad Hasan; Kontesa, Anke Afika (Pusat Unggulan IPTEK Poltekkes Kemenkes Malang, 2023)
Gadung tubers or Dioscorea hispida are tubers that originally grew in the forest and are used as alternative food ingredients to replace rice and corn. One of the preparations from gadung tubers that is popular with the community is gadung tuber crackers. Before being processed into food, gadung tubers must be processed properly so that the cyanide content is reduced. Cyanide is a goitrogenic substance that is naturally found in foodstuffs. The purpose of this study was to determine the cyanide content in gadung root crackers. In this study, 3 samples were sold in Pelem Village, Tulungagung Regency. Cyanide analysis was carried out by qualitative test using picrate paper and quantitative test using complex formation titration. The cyanide content in the sample was 2.124 mg/kg; 0.9 mg/kg; 1,386 mg/kg.